The Wiley-Blackwell companion to cultural geography - Johnson, Nuala Christina 1962- (Blackwell companions to geography., 2013)
Combining coverage of key themes and debates from a variety of historical and theoretical perspectives, this authoritative reference volume offers the most up-to-date and substantive analysis of cultural geography currently available. This book traces the historical evolution of cultural geography through to the very latest research. It covers a number of new topics such as biotechnology, rural, food, media and technology, borders and tourism, whilst also reflecting developments in established subjects including animal geographies. An accessible thematic structure features section on topics such as identities, nature and culture, and flows and mobility. The Companion is edited and written by the leading authorities in this fast-developing discipline, and features a host of new contributors to the second edition. Together they provide an international and interdisciplinary perspective, reflecting the advancing academic traditions of non-Western institutions, especially in Asia.